FRAUD THEORIES AND GLOBAL CYBERCRIME DURING THE COVID-19 PANDEMIC: THE EXTENDED S.C.C.O.R.E MODEL - Joshua, Abimbola Abosede, Alao, Olubunmi, Ige, Oludele Emmanuel (International Journal of Research Science and Management, 2023)
The study focused on the impact of present covid-19 cybercrime predicament on every facet of individual lives and organisations with the aim of elaborating the fraud theories. The paper review most widely and accepted fraud models so as to establish the motive behind why people commit fraud. Some of the fraud theories reviewed in the study include Anomie theory, Routine Activity theory, Fraud Triangle theory, Rational Choice theory, Fraud Diamond, Fraud Scale, M.I.C.E theory, the ABC of While-Collar Crime theory, Fraud Pentagon and Fraud Hexagon. The study found out the major factors causing fraudulent activities most especially in the pandemic include opportunity emanated due to the global economic crisis and thereby conclude in formulating another model S.C.C.O.R.E.E which is presented diagrammatically as the Fraud Heptagon. The study included an additional acronym E to the initial S.C.C.O.R.E which stands for the economy exploited both by individuals and firms to perpetrate fraudulent activities as a result of the pandemic which have devastating effects on the economies both in the developed and the developing countries. The study opined that the fraud theories should be updated in line with the current economic condition that birthed an outrageous rate of global cybercrime and thereby contributed to the field of theoretical development. Therefore, the paper contributes to the development of fraud theories by identifying the major motivating fraud factors which enabled the occurrence of fraud and stands as a reference point for future researches.